Model of correlation between perceived local environment and urban poverty: an evidence from Rajshahi City, Bangladesh - Md. Jahan Boksh Moral, (Universiti Kebangsaan Malaysia, 2010)
Poverty is a major cause and effect of global environmental problems. Poverty is indeed multidimensional, and the inter-linkage between environment and poverty can hardly be over emphasised. The eradication of poverty is a major development challenge. Rapid economic growth can contribute much to poverty eradication. However, fast-paced economic growth is often accompanied by adverse environmental effects. The correlation between the state of poverty and environment has been widely known, however quantitative correlation between these two is rarely undertaken. The principal objective of this study is to understand the relationship between poverty and local environmental degradation through a general model. The study is undertaken by acquiring primary data from the field survey employing a structured questionnaire and gathering information on poverty and environment nexus with emphasis on poverty and environmental degradation. Rajshahi City of Bangladesh is selected through purposive sampling as the study area in 2004. Two underserved communities of the city were explored in the study. The investigated communities named as Ramchandra Pur Shamprasharito and Bustu Hara were selected through the same sampling method. Through the stratified random sampling 50 and 100 families out of the entire 100 and 300 families respectively were chosen from the communities with significant level at 0.05. Attempt is made to correlate perceived condition of the environment by local people and environment-related variables. The result shows that environment condition and poverty is highly correlated.